Educational Management of Hypnoteaching-Based Learning Model Development in Islamic Higher Education - Subroto Subroto; Zulhammi Zulhammi; Lis Yulianti Safrida Siregar (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study addresses the persistent issue of monotonous instructional practices in Islamic Religious Education (PAI) in higher education, which tend to emphasize surface-level cognitive achievement without effectively engaging students’ subconscious dimensions. From an educational management perspective, this condition reflects limitations in instructional planning, lecturer readiness, and the systematic implementation of innovative learning models. The objective of this research is twofold: (1) to analyze existing learning conditions in the PAI Study Program, and (2) to develop a hypnoteaching-based learning model that is valid, effective, and practical within a structured management framework. This study adopts a Research and Development (R&D) approach using the ADDIE model, which integrates key managerial functions, including planning (analysis and design of the model), organizing (lecturer preparedness and instructional system support), implementation (integration of the model into classroom practice), and evaluation (validation and effectiveness testing as part of quality control). The findings indicate that the developed model achieved a high level of validity, with expert validation reaching 93%, categorized as “very valid.” In the implementation stage, the model proved to be more effective than conventional lecture-based methods, significantly enhancing students’ learning interest, engagement, and active participation. Moreover, the model contributes to a more conducive and psychologically supportive learning environment. From a management standpoint, the hypnoteaching approach supports lecturers in applying structured, persuasive communication strategies while strengthening institutional efforts in improving instructional quality and governance. It also facilitates the internalization of Islamic values through a more holistic and student-centered learning process. In conclusion, this study offers a strategic contribution to educational management by providing a systematic and applicable framework for planning, implementing, and evaluating innovative learning models in higher education